The Effectiveness of Demonstration Method in Improving The Students Speaking Skills - Payung, Aslinda Liling; Baa, Sultan; Asriati, Asriati (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This pre-experimental research involved one class that was given special treatment. The purpose of this research is to find out how effective the demonstration method is in improving the speaking skills of students in the twelfth grade of Frater High School. This research involved Frater High School students who were in the twelfth grade. In this study, a group of students from class twelve (XII), consisting of 25 students, was randomly selected. Speaking tests before and after treatment are part of the data collection process. To compare test results, data collected from the oral speaking test was analyzed quantitatively using the IBM SPSS Version 26 program.. Using a paired sample t-test before and after the material. The analysis's findings indicate that the "very poor" category is represented by an average pre-test score of 34.40 and the "fairly good" category by an average post-test score of 68. The hypothesis t-test results indicate that the research's significance value is less than 000, or less than the 0.05 level of significance. According to the pretest and post-test results, which showed t-table 2.064, df 24, and p<000, the demonstration method significantly improved the speaking abilities of Frater High School twelfth grade students. Thus, it can be said that the Frater High School twelfth grade speaking skills are improving as a result of the demonstration method..Keywords: Demonstration Method, Speaking Skills.